JETS IN 20 AGNS WITH STRONG LONG-TERM VARIABILITY OF 1 - 22 GHZ SPECTRA - Kovalev, Yu. A.; Berlin, A. B.; Kovalev, Y. Y.; Nizhelsky, N. A. (Одеські астрономічні публікації, 2017)
Results of multifrequency broad band spectra observations and their interpretations by the Hedgehog relativistic jet model are presented for 20 strong variable radio sources. The many years strong variability of well known objects, including BL Lac and OJ 287 for 20 years, is analyzed. Instantaneous 5-7 frequency spectra were measured at the RATAN-600 radio telescope over the period from 1979 to 1999. The strong long-term variability of the spectra is explained by the variability of a continuous relativistic jet with a variable ejection of it from an active nucleus in quasi radial magnetic field.